PIDANA MATI DALAM PERSPEKTIF FILSAFAT KEADILAN (Kajian Putusan Nomor 5642 K/Pid.Sus/2022 ) - Susanti, Heni; Asra Rahmad, Riadi (Desiderata Law Review, 2024)
The aim of this research is, firstly, how judges consider in deciding cases (Study of Decision Number 5642 K/Pid.Sus/2022), secondly, How the death penalty applies (Study of Decision Number 5642 K/Pid.Sus/2022), from the perspective of the philosophy of justice. This research uses a normative approach, namely by reviewing or analyzing secondary data in the form of primary, secondary and tertiary legal materials. Based on the results of the examination, the Judge was of the opinion that the Defendant and the Public Prosecutor's reasons for their cassation could not be corrected, the Judex Facti decision which stated that it was proven that the convict had committed the act of "Deliberately committing violence, forcing the Child to have sexual intercourse with him, which the Educator did, causing more than 1 (one) victim several times. ” and imposing the “death” penalty on the Defendant was appropriate and accompanied by sufficient consideration. The imposition of the death penalty for perpetrators of sexual violence, if only seen technically, means that the application of the death penalty is contrary to human rights as stated in Article 28A paragraph (1), 28I paragraph (1), in conjunction with Article 4 of Law Number 39 of 1999, in conjunction with article 3 of the UDHR. However, if studied contextually using extensive and theological interpretations, the actual application of the death penalty does not conflict with human rights.